Estudo do processo da degradação da paisagem no Jardim Aeroporto I, Município de Franca - SP - Barini, Marcelo Lemos (2010)
This current paperwork approach the gully's existence in the city of Franca - SP, that is between medium sizes urbancenters from the paulist inland that didn't pass thru the metropolitam process. The Franca's city presented an accelerated and diffuse expansion process, but do not present clandestine lots or slums. Franca is marked by the ground naturals fragility associated to the urban expansion process of lots putting these city between de paulists towns that shows the most critical problems as the highly erosive process - the gullies. This study goal was to get information that can subsides strategic formulations aiming for the recovery and conservation of the studied object, the erosive process located in the Airport's Garden I city of Franca-SP. These analysis allowed a better understood of how the erosive process are formed, that in Franca's town, appeals in discriminated way. It was possible after a biophysics characterization from Franca's town based on theme maps analyses (hydrography, geomorphology, geology, pedology, topography) associated to a bibliographic reference raising about these theme, that permitted comprise that aren't the anthropical actions the only conditionals from erosive process. Was possible observate that even with the inefficiency legislation, that approaches the whole ecological value of conservation and/or preservation, by the fact simply based on river enlargement to the delimitation of protection lanes, slighting a series of local specifications related to the water course that needs to be considerate from the rigging measures incidental above these surfaces. Concluding that the area has to be recovered in main of the vegetation around headboards and in second moment, the urban park creation proposal be studied that belongs to a green area category which characterizes themselves as a public space with meaningful dimensions and the natural elements predominance, vegetal covering mostly, that regard beyond the recreational function, normalcy recognized ecological, esthetical and educational functions. The present work deals about the existing gully in the city of Franca - SP, which is among the urban middle-sized state of São Paulo that have not gone through the process of metropolitanization.